Dialogue between law and software engineering for a new transparency paradigm: digital social control - Tavares, André Afonso; Bitencourt, Caroline Müller (Universidad Nacional del Litoral, 2021)
This work reflects, based on the dialogue between Law and Software Engineering, about the current paradigm of public transparency, so that electronic portals start to produce communication between citizens and governments, and, therefore, make it materially possible the exercise of social control. Thus, the problem faced here will seek to respond in a propositional way in which way and through which mechanisms the dialogue between the duties of public transparency and software engineering can contribute to the production of communication between the Public Administration and its citizens to make the exercise of social control through transparency portals. The hypothesis is that from the dialogue between law and software engineering, using programming languages, business intelligence techniques, big data, machine learning, artificial intelligence applied to transparency portals and data in format open access made available by the Public Administration, as determined by the Access to Information Law, communication between citizens and government can be made possible through the access made possible by the advent of the internet and the development of various instruments, such as the compilation and production of automated reports , tables, references and immediate access to documents and data of a public nature. The dialectic method was used in this research. Through the use of data provided by the Open Data project (https://dadosabertos.poa.br/), from the capital Porto Alegre / RS, for the present work, data extraction related to bids and administrative contracts (Licitacon) made by the mentioned public entity and made available in commaseparatedvalues ​​- csv format. It was possible to verify 21.946 records of bids carried out and produce some graphs that facilitate the understanding of the data. In addition to open data, it is necessary to structure and expand the Brazilian public administration itself through software engineering, based on what is currently called digital government.